(untitled) (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the effect of teachers’ perceptions of school climate on the classroom management styles they adopt. The research was conducted within the framework of a correlational survey model. The study group consisted of a total of 309 teachers working in various schools during the 2023-2024 academic year. Data were collected using the “School Climate Scale” and the “Classroom Management Styles Scale.” The data were analyzed using t-tests, one-way analysis of variance (ANOVA), and Pearson correlation analysis. According to the research findings, teachers most frequently adopted authoritarian and indifferent classroom management styles; however, they generally perceived the school climate as positive. Significant differences were found in classroom management and school climate perceptions based on demographic variables such as gender, age, marital status, education level, and years of experience. Additionally, weak but significant relationships were found between school climate sub-dimensions and classroom management styles. Components of school climate such as democracy, leadership, and success factors support positive classroom management approaches.